Influence of thermal processing on the electrical characteristics of MOS capacitors on strained-silicon substrates - Kelaidis, N.; Ioannou-Sougleridis, Vassilios; Tsamis, Christos; Krontiras, Christoforos A.; Georga, Stavroula N.; Kellerman, Bruce K.; Seacrist, Mike R.; Skarlatos, Dimitrios (My University, 2008)
In this work the influence of thermal oxidation and subsequent thermal processing on the electrical characteristics of strained-Silicon (s-Si), MOS capacitors was studied. Strained-Si/Si1 − xGex/Si substrates of two different strain levels (10% and 22% Ge content) were oxidized within the temperature range of 800 °C to 900 °C for various time intervals. Capacitance-Voltage measurements reveal that the response of the MOS capacitors depends mainly upon two factors: a) the extend of the s-Si layer oxidation, i.e. the remaining s-Si thickness and b) the duration of the post-oxidation annealing in inert ambient. Both factors influence the interfacial properties of the structures. Additional oxidation experiments in N2O ambient indicate a significant influence of the process conditions on the quality of the oxidized structures.
Keywords: Strained-Silicon; Oxidation; Thermal budget; Oxynitridation